2019
DOI: 10.1007/s41666-019-00053-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Integrated IT Support on the Prehospital Stroke Process: Results from a Realistic Experiment

Abstract: Stroke is a serious condition and the stroke chain of care is a complex. The present study aims to explore the impact of a computerised decision support system (CDSS) for the prehospital stroke process, with focus on work processes and performance. The study used an exploratory approach with a randomised controlled crossover design in a realistic contextualised simulation experiment. The study compared clinical performance among 11 emergency medical services (EMS) teams of 22 EMS clinicians using (1) a compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the initial deductive analysis, the data were sorted to reflect the six phases of an EMS mission specified by Andersson Hagiwara et al (2019): ‘receiving the call’, ‘arriving at the scene’, ‘on scene assessment and treatment’, ‘transport decision and departure’, ‘en route assessment and treatment’ and ‘handover’ (see Table 3). This ordered the data chronologically, which is one way of creating a structure for case study analyses (Yin, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In the initial deductive analysis, the data were sorted to reflect the six phases of an EMS mission specified by Andersson Hagiwara et al (2019): ‘receiving the call’, ‘arriving at the scene’, ‘on scene assessment and treatment’, ‘transport decision and departure’, ‘en route assessment and treatment’ and ‘handover’ (see Table 3). This ordered the data chronologically, which is one way of creating a structure for case study analyses (Yin, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The simulations were based on previous research [ 31 ] and were considered realistic, as found from the interviews with all participating clinicians, who expressed that the environment was familiar and the actors captured stroke patients’ symptoms well. We believe that simulation was an effective tool in safely evaluating the potential of video consultation, to attain increased understanding of how the system can be used effectively for stroke assessment, before commencing with clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate EMS clinicians’ on-scene patient assessment, we used an instrument for competence assessment by Tavares [ 29 ] and the translated and cultural adapted instrument by Bremer et al [ 30 ]. To this point, there are no clinical studies investigating prehospital patient assessment in this level of detail, hence we provide data collected in a previous study [ 31 ] on prehospital stroke assessment, using the same assessment protocol and type of simulations as we do here. Mann-Whitney U tests were used to determine differences between the historical baseline group and the group participating in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…This test showed that the different systems could communicate with each other effectively without failures. In the last phase, the system was tested in a full-scale realistic operational simulation (roleplay), where an entire ambulance mission from dispatch to handover was simulated [13]. Eleven ambulance teams (22 ambulance clinicians) were recruited to the study.…”
Section: Methodsmentioning
confidence: 99%
“…Eleven ambulance teams (22 ambulance clinicians) were recruited to the study. The teams were instructed to either start using a computerized decision support system (CDSS), described in [13], or to work as usual. Two representative patient cases with stroke-like symptoms were created.…”
Section: Methodsmentioning
confidence: 99%